The route to radicalisation for Malay-Muslim women : tracing the Nexus between universals and particulars in Malaysia - Sukhani, Piya (Nanyang Technological University, 2020)
Since the emergence of the Islamic State in Iraq and Syria (ISIS) in 2013, the number of Malaysian women joining the militant group in conflict zones began growing, with some even being prepared for suicide bombing missions. However, Malay-Muslim women joining ISIS generally retained their conservative conception of gender roles. In examining why this conception holds, this paper looks at the socio-cultural and political context of Malaysia. It posits that the Islamisation of Malaysia and state-driven narratives about Malay-Muslim supremacy have in fact served to undercut ISIS’s appeal. The paper ends by cautioning that continued vigilance is necessary nonetheless, given growing political and economic instability, both locally and globally, which could undermine the state’s legitimacy at the expense of ISIS.